Héroes a medio tiempo - Arroyo, Justo 1936- (Universidad Tecnológica de Panamá, 1998)
Eleven stories in which literature of the fantastic and experimental techniques morph into one another to produce fairly compact narratives. Arroyo tends to portray types (the functional drunks in "Los sueÑos de SepÚlveda" and the title story, the nasty waiter, the clumsy man, etc.) rather than particular individuals. Humor is not absent from stories like "Por qué, Vivian?", which is the best of the collection.